SOCIAL REPRESENTATIONS OF HUMANIZATION IN HOSPITAL PEDIATRICS AMONG HEALTH PROFESSIONALS - CAMILA BATISTA NOBREGA PAIVA CAMILA (Psicologia em Estudo, 2023)
Humanization aims at transforming the institutional model of health by valuing the subjective, historical and socio-cultural aspects of health and disease processes. However, because it carries multiple meanings, its implementation has been a challenge in several public health services. Therefore, this study aimed to apprehend the social representations about humanization in pediatrics among health professionals who work in this context. It is a qualitative research, carried out in a university hospital in the northeast, with the participation of twelve health professionals from eight categories. To apprehend the data, a semi-structured interview was used, whose data were analyzed through thematic categorical analysis. The data allowed the construction of three thematic categories: the context of pediatrics, care practices and humanization. It was found that although it is gratifying to work in pediatrics, there are difficulties in the relationships between the professionals themselves and between the professionals and the caregivers of the children. Care practices are mainly supported by humanistic values ​​expressed in affective ties and in the effective use of clinical reasoning and materials. Humanization, in turn, was represented predominantly by humanistic values, although there are some representational elements that refer to aspects of the National Humanization Policy. The absence of arguments based on the user's right to quality assistance was found. Therefore, it is necessary to take actions that can promote reflections and strategies in humanization, in order to promote new meanings in the way of thinking and concretizing the proposal of humanization in health.